Revitalization of Nahwu Learning: Utilization of the Book Al-Fushul Al-Fikriyah as Innovative Teaching Material in Islamic Boarding School Environments - Mufarihah, Siti Barikatul; Rahman, Rifqi Aulia; Mukromin, Mukromin (AJIRSS: Asian Journal of Innovative Research in Social Science, 2024)
Nahwu instruction in Islamic boarding schools often faces challenges regarding the relevance of the approach and students’ comprehension of Arabic grammatical rules, which tend to be abstract and rigid. This study aims to describe an innovative Nahwu learning method through the utilization of the Al-Fushul Al-Fikriyah book by Shaykh Abdullah Basha Fikri, known for its systematic deductive approach and Malay-Arabic linguistic style. The research employs a descriptive qualitative method, using observation, in-depth interviews, and documentation for data collection.The findings reveal that this kitab provides a more contextual learning experience by starting with the presentation of grammatical rules, followed by practical explanations and relevance to students’ daily lives. The book is considered communicative, direct, and structured, which facilitates students in comprehending Nahwu concepts more effectively. This is evidenced by increased student engagement, better understanding of grammatical structures, and enthusiastic participation in classroom discussions.This innovation proves to be effective in improving the quality of Nahwu learning in pesantren settings. The study recommends the adoption of a systematically-contextualized kitab as a strategic alternative for developing Arabic grammar instruction, especially in pesantren and Islamic educational institutions that implement traditional kitab kuning-based curricula.